Samuderamaps: water quality management library for conservation and sustainable use of marine resources and ecosystems - Kamaruddin, Sharir Aizat; Abd. Aziz, Khairul Naim; Roslani, Muhammad Akmal; Zainol, Zamzila Erdawati; Ahmad, Aziani; Tajam, Jamil (Universiti Teknologi MARA, Kedah, 2022)
Major pollutants such as untreated sewage and chemical run-off can degrade the health and safety of humans, marine organisms, and ecosystems. Tackling marine water quality must start immediately, especially when marine resources are at high risk. There are few available water quality maps, especially in the Northern regions of Malaysia. SAMUDERAMAPS’s aims to provide spatialtemporal information on water quality data for the conservation and sustainable use of marine resources and ecosystems. SAMUDERAMAPS was created by integrating the most recent data on physicochemical water parameters with Geographic Information System (GIS) technologies. SAMUDERAMAPS is a ready-made product containing water quality maps of physicochemical water parameters, including water nutrient parameters, for the Kedah regions such as Sungai Kilim, Pantai Kok, Pulau Dayang Bunting, Pulau Tuba, and Sungai Merbok. SAMUDERAMAPS provides a selection of paper and digital maps at a reasonable price. These maps are designed to meet the needs of a wide range of customers, including social and economic players, thus for local communities as well. SAMUDERAMAPS can assist environmentalists in monitoring water quality parameters, resources and ecosystems in difficult-to-reach or highly biodiverse areas. SAMUDERAMAPS also assists with site selection and hotspot analyses to promote the long-term sustainable development of mariculture regions, coastal tourism destinations, marine transportation activities, and fishing operations. SAMUDERAMAPS is consistent with the Sustainable Development Goals established by the United Nations SDG 14: "Life below water," SDG 2: "Zero hunger," SDG 3: "Good health and well-being," and SDG 13: "Climate action".